EKSISTENSI PEREMPUAN DALAM REALITAS HISTORIS ISLAM - Munir, Misbahul Munir; Furziah, Furziah (NOURA: Jurnal Kajian Gender dan Anak, 2022)
This paper examines the existence of women in the reality of Islamic history. This paper attempts to explore and reveal information about women through the holy texts of the Qur’an, hadiths, and interpretation of mufasir. In historical facts, both before the presence of Islam or even after its presence, there are often many imbalances in views, recognition and acceptance of the existence of women in a sosial order of society. Discriminatory treatment of women does not only occur in the Islamic religion, but also in other religions, this problem is also an issue that demands to be resolved. This happens because of a misunderstanding in understanding religiuos texts. The tendency to understand the text of the Qur’an and hadith haphazardly without using the rules of interpretation will result in misinterpretation of the text or even deviate from what the text wants.